The best employee Of the year using pythagorean fuzzy numbers / Noraini Ahmad and Wan Nurul Anis Shaziela Wan Azilan - Ahmad, Noraini; Wan Azilan, Wan Nurul Anis Shaziela (UiTM Press, 2021)
In the context of any jobs, employees play an important role in the development of an organization. The success of any organization is significantly dependant on the quality of their employees. Thus, employers should always ensure that their employees are motivated, hence their efforts and work performances will be optimized. Employee performance appraisal is one of the ways to motivate employees, in which employers appreciate their employees by offering promotions, introducing recognition awards such as the best employee awards or rewarding them by remuneration in forms of bonuses or yearly vacations. The process of selecting the best employee is very vital and are evaluated based on the standards criteria, sets by the company and usually made by top managements. Based on previous research, selection of the best employee of the year was usually modelled by using the analytic hierarchy process (AHP) based on crisp number. The same method is applied for this current research, but it was extended using Pythagoras Topsis (PFTOPSIS) model based on fuzzy scale. A model was developed using Analytic Pythagorean Fuzzy Number (PFN) which uses both qualitative and quantitative decision making approaches. In this approach, a score function based comparison method was proposed to identify the Pythagorean fuzzy positive ideal solution and the Pythagorean fuzzy negative ideal solution. Afterward, a revised closeness was introduced to identify the optimal alternative. This model considered 4 criteria and 22 sub-criteria to be evaluated in ranking the best employee of the year. The results show that the qualities of works contributes significantly on the evaluation of the best employee of the year.